Prognostic Value of C-Reactive Protein, Leukocytes, and Vitamin D in Severe Chronic Obstructive Pulmonary Disease. (21st January 2014) - Moberg, Mia; Vestbo, Jørgen; Martinez, Gerd; Lange, Peter; Ringbaek, Thomas
Abstract : Inflammatory biomarkers predict mortality and hospitalisation in chronic obstructive pulmonary disease (COPD). Yet, it remains uncertain if biomarkers in addition to reflecting disease severity add new prognostic information on severe COPD. We investigated if leukocytes, C-reactive protein (CRP), and vitamin D were independent predictors of mortality and hospitalisation after adjusting for disease severity with an integrative index, the i-BODE index. In total, 423 patients participating in a pulmonary rehabilitation programme, with a mean value of FEV1 of 38% of predicted, were included. Mean followup was 45 months. During the follow-up period, 149 deaths (35%) were observed and 330 patients (78.0%) had at least one acute hospitalisation; 244 patients (57.7%) had at least one hospitalisation due to an exacerbation of COPD. In the analysis (Cox proportional hazards model) fully adjusted for age, sex, and i-BODE index, the hazard ratio for 1 mg/L increase in CRP was 1.02 ( P = 0.003 ) and for 1 × 10 9 / L increase in leukocytes was 1.43 ( P = 0.03 ) . Only leukocyte count was significantly associated with hospitalisation. Vitamin D was neither associated with mortality nor hospitalisation. Leukocytes and CRP add little information on prognosis and vitamin D does not seem to be a useful biomarker in severe COPD in a clinical setting.